Feasibility and safety of single-pulse ablation in 20 patients with atrial fibrillation - Loh, Peter; Groen, Marijn H A; Taha, Karim; Velthuis, Birgitta K; Fidder, Herma H; Vink, A; Wittkampf, Fred H M; Doevendans, Pieter A F M; van Es, René (Heart rhythm, 2025)
Single-pulse ablation leads to irreversible electroporation (IRE) and has been introduced as a nonthermal ablation technology for pulmonary vein isolation (PVI). First-in-human studies demonstrated the acute feasibility and safety of IRE PVI. This study aimed to further investigate the safety of single-pulse ablation for PVI. Twenty patients with symptomatic atrial fibrillation underwent single-pulse PVI under conscious sedation. Nonarcing, nonbarotraumatic, 6 ms, 200 J IRE applications were delivered via a custom 14-polar circular IRE ablation catheter with a variable hoop diameter (16-27 mm). Adenosine testing was performed after a 30-minute waiting period. On day 1 after ablation, patients underwent esophagoscopy and brain magnetic resonance imaging (MRI) (diffusion-weighted imaging/fluid-attenuated inversion recovery). In 20 patients, all pulmonary veins could be successfully isolated with a mean of 11.8 ± 1.4 IRE applications per patient. One pulmonary vein reconnection occurred during adenosine testing; reisolation was achieved with 2 additional IRE pulses. No periprocedural complications were observed. Brain MRI on day 1 after ablation showed punctate asymptomatic lesions in 3 of 20 patients (15%). At follow-up MRI, the lesion disappeared in 1 patient whereas 1 lesion persisted in the other 2 patients. Esophagoscopy on day 1 showed an asymptomatic esophageal lesion in 1 of 20 patients (5%); at repeat esophagoscopy on day 22, the lesion had resolved completely. Acute electrical PVI could be achieved safely and rapidly. Acute silent cerebral lesions were detected in 3 of 20 patients (15%) and may be caused by ablation or changes of therapeutic and diagnostic catheters over a single transseptal access.